Property rights, labor reallocation, and gender inequality in rural China - Shi, Xinjie; Huangfu, Bingyu; Jin, Songqing; Gao, Xuwen (Journal of economic behavior & organization, 2024)
This study examines the gender-differentiated effects of improved land property rights on labor reallocation in China, using quasi-exogenous variation in the timing of the implementation of the Rural Land Contracting Law, which allows farmers to lease out their land. We find that while men and women tend to shift labor from the agricultural into non-agricultural sector following the land reform, women lag behind men. Our findings reveal a noticeable gender gap in the growth of off-farm labor participation (+16.69 % among men; + 1.95 % among women) and hours worked in off-farm sectors. The gender-differentiated effects on off-farm employment are likely caused by disadvantaged labor market conditions for women. These findings underscore the importance of improved land property rights in fostering rural structural transformation. Moreover, our results suggest that implementing land reforms without accompanying changes to address the root causes of gendered differences in off-farm employment could limit their full potential. This study has significant policy implications for the rural transformation of developing countries.